1997
DOI: 10.1006/viro.1996.8304
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Baculovirus-Encoded Protein with the Capsid Basal Region

Abstract: An open reading frame homologous to AcMNPV ORF9 (ORF1629) was characterized in the Orgyia pseudotsugata multinucleocapsid nuclear polyhedrosis virus (OpMNPV). Sequence analysis indicated that the OpMNPV homolog (called ORF2) encoded a protein predicted to contain 545 amino acids with a molecular weight of 61 kDa. The first 80 amino acids did not have a counterpart in the AcMNPV homolog. The remainder of the ORF was poorly conserved with 29% amino acid identity overall with the AcMNPV ORF. However, the amino te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Gold particles appeared to be distributed over the cylindrical capsid sheath of nucleocapsids, which is similar to the localization pattern of the major capsid shell protein VP39 (37). The localization pattern of 38K is different from that of PP78/83, which is associated with the ends of the capsids containing the basal structure (36); from that of PP31, which is associated with the electron-condensed matte (14); and from that of ODV-E66, which is associated with the intranuclear microvesicles and the envelope of ODV (17). So the distribution of 38K suggests that it may be a capsid shell protein associated with VP39 and other nucleocapsid proteins.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Gold particles appeared to be distributed over the cylindrical capsid sheath of nucleocapsids, which is similar to the localization pattern of the major capsid shell protein VP39 (37). The localization pattern of 38K is different from that of PP78/83, which is associated with the ends of the capsids containing the basal structure (36); from that of PP31, which is associated with the electron-condensed matte (14); and from that of ODV-E66, which is associated with the intranuclear microvesicles and the envelope of ODV (17). So the distribution of 38K suggests that it may be a capsid shell protein associated with VP39 and other nucleocapsid proteins.…”
Section: Discussionmentioning
confidence: 69%
“…The capsid sheath is formed by stacked ring-like subunits consisting of one major polypeptide, VP39, together with several minor proteins (38). It was proposed that PP78/83, BV/ ODV-C42, and ODV-EC27 form a complex at the nucleocapsid base because electron microscopy revealed that PP78/83 is associated with the nucleocapsid base, and BV/ODV-C42 interacts directly with PP78/83 and ODV-EC27 (5,36,38). Several additional minor proteins have also been identified to be associated with the nucleocapsid, including PCNA (2), VP1054 (31), FP25 (4,18,35,48), VLF-1 (22,27,29,42,43,50), VP80 (21,25,30), and P24 (47).…”
mentioning
confidence: 99%
“…To confirm that the interactions predicted by yeast two-hybrid analysis reflected interactions which occurred in vivo, blue native gel and Western blot analysis was performed using fractions prepared from infected cells (28 h p.i.). This analysis showed that C42 and p78/83 (p78/83 is also a structural protein of baculovirus [18,21]) comigrate, consistent with complex formation, and that they are present in two complexes, a complex at 180 kDa and a larger complex (approximately 500 to 600 kDa) that also contains EC27.…”
Section: Discussionmentioning
confidence: 79%
“…Sequence analysis confirmed that the construct was in frame. The fusion protein was expressed, isolated, and used for inducing rabbit polyclonal antiserum as previously described (35). The immune serum used in this report was collected 8 days after the fifth boost.…”
Section: Methodsmentioning
confidence: 99%